A basic study on standardization of fire-fighting drill scenarios on board. Issue 3 (2nd October 2019) - Sim, Hyosang; Ha, Weon-Jae; Park, Young-Soo
ABSTRACT: Fire-fighting drill is conducted by the crew assuming that fire is occurred on board; in most cases, engine room drill is carried out due to high possibility of fire occurrence. In general, fire-fighters attempt to extinguish the fire and if fail, the fixed fire extinguishing system is operated. In this connection, fire drill scenario is very important not only for improving crew's fire-fighting competency but also for fire-fighters' safety. During the drill, captain should decide fire-fighters' entry and withdrawal. However, in most vessels, the time to withdraw from the fire scene is not indicated, but the decisions are left to the fire-fighters based on the air bottle's low pressure alarm. In this study, for a basic study on standardization of fire-fighting drill scenarios, by the experiments on the training ship with apprentice officers and analysis of ship's drawings, the time required for crew assembling, the arrival time to fire scene, the time to wear fire-fighter's outfit, the moving time of fire-fighters in fire scene depending on the flat ground or the stairs, and the water pressure in fire hose were considered. Moreover, the allowable time for fire-fighting work was estimated by analysis of working time limitation based on the air consumption of the self-contained breathing apparatus. As a result, basic model standard fire-fighting drill scenario was developed showing the action guideline according to the time elapsed. The model standard scenario can be modified by each ship's circumstance, and this will be a great assistance to ensure the safety of fire-fighters and ship.